Challenges of Training Institutions in Accelerating The Availability of Graphic Design Online Classes for Trainees - Umaro, Mada; Triana Rejekiningsih; Deny Tri Ardianto (Journal of Education Technology, 2022)
The digital era is currently affecting activities in the world of training. This study investigates the challenges training institutions face in accelerating the availability of online classes for today's trainees. This research uses a descriptive qualitative approach. A total of 126 participants came from graphic design training participants. Then, the data collected in this study was by distributing a 4-scale questionnaire, pretest-posttest assessment, and using a Likert Scale observation sheet with five scales (0-4). The results showed that the participants had a reasonable opinion of the availability of online classes at training institutions on the aspects of mastery of the material by the instructor, the accuracy of the presentation, the relevance of the training content, and its suitability for the needs of the training participants. The significance value based on age range, gender, and graduate status is 0.863, 0.094, and 0.107. The results of the pretest-posttest assessment also increased when using online classes. Positive results also impact training participants in understanding graphic design material as a whole with the availability of online courses at training institutions. The presence of this online class has had many positive influences in all aspects but still needs improvement because there are challenges that need to be resolved by the Training Institute. The faster the availability of online classes at the Training Institute, the quicker the fulfillment of training needs.